EUS Guided Through the Needle Biopsy Versus Fine Needle Aspiration for Pancreatic Cystic Lesions: : A Systemic Review and Meta-analysis - Sayeh, Wasef (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.